2020
DOI: 10.1038/s41598-020-69981-1
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine production in patients with recurrent acute tonsillitis: analysis of tonsil samples and blood

Abstract: the aim of this study was to examine t cell function in tonsils of patients with recurrent acute tonsillitis (RAT) or peritonsillar abscess (PTA) by analyzing the cytokine production following T cell receptor (TCR) and co-receptor stimulation with a combination of anti-CD3 and anti-CD28 antibodies. The release of IFN-γ, TNF-α, IL-2, IL-4, IL-6, IL-10 and IL-17A from isolated, stimulated T cells of 27 palatine tonsils (10 RAT, 7 PTA, 10 tonsils without inflammation) was measured via a bead-based flow cytometric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 22 publications
1
13
0
1
Order By: Relevance
“…Stimulation increases the pro-inflammatory cytokines TNF-α, IFN-γ and IL-2 more than the anti-inflammatory cytokines IL-4 and IL-10 in tonsil and blood samples in RAT, PTA and noninflammatory samples. The blood of patients with tonsillitis showed higher levels of proinflammatory cytokines compared to the samples of non-inflammatory patients [24]. The present study has also reported this finding.…”
Section: Discussionsupporting
confidence: 87%
“…Stimulation increases the pro-inflammatory cytokines TNF-α, IFN-γ and IL-2 more than the anti-inflammatory cytokines IL-4 and IL-10 in tonsil and blood samples in RAT, PTA and noninflammatory samples. The blood of patients with tonsillitis showed higher levels of proinflammatory cytokines compared to the samples of non-inflammatory patients [24]. The present study has also reported this finding.…”
Section: Discussionsupporting
confidence: 87%
“…According to the design, patients with Paradise criteria were not included in our study, i. e. the issue of tonsillectomy was not considered [6,7]. Thus, it was possible to monitor patients for a long time and determine the clinical efficacy of the studied treatment regimens in relation to the recurrence rate of tonsillitis.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnostic and differential diagnostic criteria for acute tonsillitis were carried out in accordance with the DEGA M recommendations provided in clinical guidelines [2,6]. A clinical diagnosis of AT was established in the presence of such symptoms as sore throat at rest and in swallowing, hyperaemia and swelling with possible plaque on the tonsils, cervical lymphadenitis and fever.…”
Section: Participantsmentioning
confidence: 99%
See 2 more Smart Citations